Synthesis, structure and properties of complex compounds of cobalt, nickel, copper and zinc with 2-formylpyridine semicarbazone [Articol] - Gulea, Aurelian; Gînju, Dumitru; Bairac, Natalia; Poirier, Donald; Țapcov, Victor (My University, 2009)
2-Formylpyridine semicarbazone L reacts with cobalt, nickel, copper and zinc chlorides, nitrates and perchlorites to form coordination compounds of compositions ML2X2•nH2O (M=Co, Ni, Cu, Zn; X = Cl, NO3, ClO4; L = NC5H 4-CH=N-NH-C(O)-NH2; n = 0, 1) and CuLX2• nH2O (X = Cl, Br, NO3; n = 0-0.5). Complex CuL(NO 3)2 has polynuclear, CuLX2•0.5H 2O (X = Cl, Br), binuclear, and other compounds, mononuclear structures. Azomethine L behaves in them as tridental N,N,O-ligand. Thermolysis of these complexes proceeds through such stages as dehydration (80-95°C), deactivation (145-155°C) and complete theral degradation (170-590°C). Complexes CuLX2•nH2O (X = Cl, NO3; n = 0-0.5) were established to inhibit in vitro the growth and reproduction of 100% of cancer cells of human mieloid leukaemia HL-60 at 10-4 M concentration. At 10-5 M concentration they inhibit only 10% of cells, and at 10-6 M concentration they do not possess anticancer activity.
Keywords: General Chemistry; Coordination compound; Copper atoms; Complex Versus; Zinc Chloride